Genetic inactivation of mitochondria-targeted redox enzyme p66ShcA preserves neuronal viability and mitochondrial integrity in response to oxidative challenges - Forte, Michael; Bourdette, Dennis; Su, Kimmy (Frontiers in Physiology, 2012)
Mitochondria are essential to neuronal viability and function due to their roles in ATP production, intracellular calcium regulation, and activation of apoptotic pathways. Accordingly, mitochondrial dysfunction has been indicated in a wide variety of neurodegenerative diseases, including Alzheimer’s disease, Huntington’s disease, amyotrophic lateral sclerosis, stroke and multiple sclerosis (MS). Recent evidence points to the permeability transition pore (PTP) as a key player in mitochondrial dysfunction in these diseases, in which pathologic opening leads to mitochondrial swelling, rupture, release of cytochrome c, and neuronal death. Reactive oxygen species (ROS), which are inducers of PTP opening, have been prominently implicated in the progression of many of these neurodegenerative diseases. In this context, inactivation of a mitochondria-targeted redox enzyme p66ShcA (p66) has been recently shown to prevent the neuronal cell death leading to axonal severing in the murine model of MS, experimental autoimmune encephalomyelitis (EAE). To further characterize the response of neurons lacking p66, we assessed their reaction to treatment with oxidative stressors implicated in neurodegenerative pathways. Specifically, p66-knockout (p66-KO) and wild-type (WT) neurons were treated with hydrogen peroxide (H2O2) and nitric oxide (NO), and assessed for cell viability and changes in mitochondrial properties, including morphology and ROS production. The results showed that p66-KO neurons had greater survival following treatment with oxidative stressors and generated less ROS when compared to WT neurons. Correspondingly, mitochondria in p66-KO neurons showed diminished morphological changes in response to these challenges. Overall, these findings highlight the importance of developing mitochondria-targeted therapeutics for neurodegenerative disorders, and emphasize p66, mitochondrial ROS, and the PTP as key targets for maintaining mitochondrial and neuronal integrity.